Serological Evidence and Risk Factors for Swine Influenza Infections among Chinese Swine Workers in Guangdong Province. - Mengmeng Ma; Benjamin D Anderson; Tao Wang; Yingan Chen; Dingmei Zhang; Gregory C Gray; Jiahai Lu (PLoS ONE, 2015)
During July to September 2014, we performed a controlled, cross-sectional, seroepidemiologic study among 203 swine workers and 115 control subjects in Guangdong Province. Sera were tested using a hemagglutination inhibition assay against locally-isolated swine H3N2 and H1N1 viruses and commercially-obtained human influenza viral antigens. We found swine workers had a greater prevalence and odds of seropositivity against the swine H3N2 virus (17.3% vs. 7.0%; adjusted OR, 3.4; 95% CI, 1.1 -10.7). Younger age, self-report of a respiratory illness during the last 12 months, and seropositivity against seasonal H3N2 virus were identified as significant risk factors for seropositivity against swine H3N2 virus. As swine workers in China may be exposed to novel influenza viruses, it seems prudent for China to conduct special surveillance for such viruses among them. It also seems wise to offer such workers seasonal influenza vaccines with a goal to reduce cross-species influenza virus transmission.